Exploring the dielectric and conduction characteristics of iodine substituted CaCu3Ti4O12-xIx - Yadav B.; Kar K.K.; Ghorai M.K.; Kumar D. (My University, 2025)
AC electrical measurements were carried out on iodine doped, CaCu3Ti4O12-xIx (x = 0, 0.005, 0.05 and 0.2) ceramic specimens sintered at 1100 °C for 12 h in the temperature (300–450 K) and frequency (20 Hz - 1 MHz). The crystalline structure, microstructure, and oxidation state of various ions of pure and iodine-substituted sintered specimens were carried out through XRD, SEM, and XPS, respectively. The dielectric relaxations in grains, grain boundaries, and sample-electrode interfaces for different compositions were investigated through impedance and modulus spectroscopic techniques and were reported in the first part of the investigation. It revealed the involvement of similar types of charge carriers in conduction and relaxation processes in grains and grain boundaries, respectively. This second section emphasizes the dielectric and conduction properties of CaCu3Ti4O12 (CCTO) with iodine doping at the anion site. The XPS study reveals that the concentration [VO••] is reduced, and [VM″] gets increased with increasing concentration of iodine from x = 0.05 to 0.2. This observation also supports the point defect model as reported earlier for charge compensation of impurity defect IO• i.e., with increasing substitutions of iodine, the charge on IO• change from electronic to cationic vacancies, VTi//// or copper VCu// or both to keep electrical charge neutrality. The metal ions get segregated at grain boundaries. This, in turn, will minimize hopping due to electrons between Ti4+ and Ti3+ or Cu2+ and Cu1+. As a result, it increases resistivity and minimizes dielectric losses for the higher concentration of iodine doping. Thus, a high concentration of iodine doping at the oxygen site promotes the formation of a barrier layer capacitor. © 2022 Elsevier Ltd and Techna Group S.r.l.